2014
DOI: 10.1097/meg.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of faecal M2-PK and FIT in a population-based bowel cancer screening cohort

Abstract: The addition of M2-PK in a biennial bowel screening programme is acceptable to patients, feasible and detects additional adenomas, potentially at an earlier stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Another possibility would be the use of both tests in combination although the cost effectiveness of this strategy needs to be determined. A study by Leen at al [ 23 ] found that the addition of the quantitative M2-PK test to the standard FIT detected additional adenomas at an earlier stage…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility would be the use of both tests in combination although the cost effectiveness of this strategy needs to be determined. A study by Leen at al [ 23 ] found that the addition of the quantitative M2-PK test to the standard FIT detected additional adenomas at an earlier stage…”
Section: Discussionmentioning
confidence: 99%
“…Overall, positivity was significantly increased by the addition of tM2-PK (27%). Had only i-FOBt been tested, 77% (n=189) fewer patients would have had a positive faecal test and been identified for a screening colonoscopy and 70% (n=35) fewer patients would have had polyps detected and removed [20]. This study also reported that 10% (n=99) of tM2-PK samples could not be analysed, because of a lapse in the 48 hour window required for its processing.…”
Section: Discussionmentioning
confidence: 92%
“…However, previous studies were performed on symptomatic patients recruited in clinical settings. Leen and colleagues performed the first study to assess the performance of fecal M2-PK addition to FIT-based screening program ( 10 ). The authors reported a significant improvement in ADR leading to the identification and removal of 70% more polyps.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies have evaluated fecal M2-PK levels for CRC detection in high-risk or symptomatic populations ( 6 , 9 ). However, only few studies have investigated the performance of fecal M2-PK in CRC screening programs involving potentially healthy subjects ( 10 ). Moreover, no data on fecal M2-PK efficacy in the first-round screening programs performed under real practice conditions are available.…”
Section: Introductionmentioning
confidence: 99%